The Effect of Using Reciprocal Teaching Strategy on Students' Reading Comprehension and Attitude toward Reading in Seventh Grade Students in Kuwait - Hend A. Almaian (Sultan Qaboos University, 2013)
The purpose of this study was to investigate the effect of using reciprocal teaching strategy on reading comprehension and on students' attitude toward reading for seventh grade students in Kuwait. The research sample consisted of 40 students distributed in two groups. The experimental group 20 was taught using reciprocal teaching strategy, while the control group 20 was taught using traditional methods. Two instruments were designed: a test to measure students reading comprehension and the other to measure the attitude toward reading. The results showed that there are significant statistical differences in test scores between the experimental group and the control group in favor ofthe experimental group. However, there were no significant statistical differences in students' attitudes between the two groups. The study recommends that teachers in schools use reciprocal teaching strategy in teaching reading in order to develop students' reading comprehension.